Impact of Agricultural Inputs on Indigenous Livelihoods: Evidence from Rural Makwanpur - Bastola , Pravin (International Research Journal of MMC, 2026)
Agricultural subsidy programs and agricultural input support initiatives are seen effective in transforming rural livelihoods, particularly among the indigenous and marginalized households. Using a quantitative, non-experimental, descriptive research design this study examines the efficiency of agricultural input support on indigenous livelihoods in Raksirang Rural Municipality, Makwanpur District, Bagmati Province, Nepal. Agricultural input support has made a positive contribution to the improvement of households, although the change in income is not uniform across households. Primary data was collected in 2025, with the sample of 180 households from the population of 330 households using stratified random sampling method. Where necessary, secondary data and information are from published journal articles, other literary articles and knowledge documents available in the sector. Almost 50% of the households gained income with the average income of Nepalese Rupees 12216.77 and 36% of households reported increase in annual income within the timeframe of 6 to 24 months of receipt of agricultural inputs. Larger proportion of households experienced improved food security, health and nutrition benefits and reduced household expenditure though they did not realize increase in annual income through agricultural products. Income from the sale of agricultural products was used for family livelihood, health, education with some reinvestment in agribusiness expansion and loan repayment, which indicates the shift towards livelihood diversification or creating alternative option of livelihood enhancement. The study is significant to understand the efficiency and effect of small scale external agricultural input support on family income, expenditure patterns and economic resilience reducing vulnerabilities.